Trimethyl Chitosan Nanoparticles Encapsulated Protective Antigen Protects the Mice Against Anthrax - Malik, Anshu; Gupta, Manish; Mani, Rajesh; Gogoi, Himanshu; Bhatnagar, Rakesh (Frontiers in Immunology, 2018)
Anthrax is an era old deadly disease against which there are only two currently available licensed vaccines named Anthrax Vaccine Adsorbed (AVA) and precipitated (AVP). Though they can provide a protective immunity, their multiple side-effects owing to their ill-defined composition and presence of toxic proteins (LF and EF) of Bacillus anthracis, the causative organism of anthrax, in the vaccine formulation makes their widespread use objectionable. Hence, an anthrax vaccine that contains well-defined and controlled components would be highly desirable. In this context, we have evaluated the potential of various vaccine formulations comprising of Protective Antigen (PA) encapsulated trimethyl-chitosan nanoparticles (TMC-PA) in conjunction with either CpG-C ODN 2395(CpG) or Poly I:C. Each formulation was administered via three different routes, viz., subcutaneous (SC), intramuscular (IM) and intraperitoneal (IP) in female BALB/c mice. Irrespective of the route of immunization, CpG or Poly I:C adjuvanted TMC-PA nanoparticles induced a significantly higher humoral response (total serum IgG and its isotypes viz., IgG1, IgG2a, and IgG2b), compared to their CpG or Poly I:C PA counterparts. This clearly demonstrates the synergistic behavior of CpG and Poly I:C with TMC nanoparticles. The adjuvant potential of TMC nanoparticles could be observed in all the three routes as the TMC-PA nanoparticles by themselves induced IgG titers (1-1.5 x105) significantly higher than both CpG PA and Poly I:C PA groups (2-8x104). The effect of formulations on T-helper (Th) cell development was assessed by quantifying the Th1-dependant (TNF-α, IFN-γ, and IL-2), Th2-dependant (IL-4, IL-6, and IL-10) and Th17-type (IL-17A) cytokines. Adjuvanation with CpG and Poly I:C, the TMC-PA nanoparticles triggered a Th1 skewed immune response, as suggested by an increase in the levels of total IgG2a along with IFN-γ cytokine production. Interestingly, the TMC-PA group showed a Th2 biased immune response. Upon challenge with the Bacillus anthracis Ames strain, CpG and Poly I:C adjuvanted TMC-PA nanoparticles immunized via the SC and IM routes showed the highest protective efficacy of ~83%. Altogether the results suggest that CpG or Poly I:C adjuvanted, PA-loaded TMC nanoparticles could be used as an effective, non-toxic, 2nd generation subunit-vaccine candidate against anthrax.